2015
DOI: 10.3329/baj.v17i1.23680
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spacing on P and Zn uptake of local T. Aman rice varieties in Khulna area

Abstract: A field experiment was conducted at the Agronomy field of Khulna University, Khulna during T. Aman season to evaluate the effects of spacing on nutrient content and total uptake of phosphorus and zinc by grain and straw of traditional rice of Khulna region. The experiment was laid out in split-plot design with three replications assigning three varieties viz., Jotai, Bashfulbalam, Ranisalute and three spacings viz., 30 cm x 30 cm, 40 cm x 40 cm and 50 cm x 50 cm. The variety was assigned in main plot and spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…The results are in agreement with the fi ndings of Mian, et al [24]. Similar pattern of N (91.23-133.62 kg/ha), P (17.17-21.49 kg/ha), K (66.38-106.30 kg/ha), S (7.73-12.06 kg/ ha) and Zn (0.288-0.618 kg/ha) uptake was observed by other investigators [25][26][27][28][29]. The results concluded that higher C input and nutrients uptake improved yield components of rice in border rows, contributed to higher grain yield (8%).…”
Section: Carbon Input and Uptake Of Other Nutrientsupporting
confidence: 84%
“…The results are in agreement with the fi ndings of Mian, et al [24]. Similar pattern of N (91.23-133.62 kg/ha), P (17.17-21.49 kg/ha), K (66.38-106.30 kg/ha), S (7.73-12.06 kg/ ha) and Zn (0.288-0.618 kg/ha) uptake was observed by other investigators [25][26][27][28][29]. The results concluded that higher C input and nutrients uptake improved yield components of rice in border rows, contributed to higher grain yield (8%).…”
Section: Carbon Input and Uptake Of Other Nutrientsupporting
confidence: 84%
“…Maximum nitrogen concentration was observed at the high spacing of tuberose 36 . In rice, higher P uptake was reported by Parvin et al 37 at wider spacing 37 . Higher Zn and Mg contents of tubers were also observed at the widest spacing.…”
Section: Discussionmentioning
confidence: 72%